Adaptive multivariate reusable launch vehicles reentry attitude control with pre-specified performance in the presence of unmatched disturbances - Ge, Tianshuo; Chai, Runqi; Zhu, Qinghua; Chen, Kaiyuan; Tsourdos, Antonios; Farhan, Ishrak M. D. (Elsevier, 2024)
This paper introduces a novel adaptive multivariable attitude control method for a reusable launch vehicle (RLV) to track desired attitude trajectories in the presence of unknown external disturbances and uncertainties. Unlike most existing designs that overlook mismatched disturbances, this method employs an adaptive finite-time observer (AFO) to estimate the unknown states. Based on the outputs of the AFO and the prescribed performance function, a time-varying adaptive gain that is not overestimated is designed to establish the adaptive multivariable attitude control for the RLV system. The simulations demonstrate that the proposed approach successfully guides the RLV to follow desired attitude signals despite the presence of unmatched disturbances and uncertainties.
Keywords: Finite time convergence; Chattering attenuation; Adaptive multivariable control; Attitude control of reusable launch vehicle (RLV); Pre-specified performance